Use and abuse of authority: A behavioral foundation of the employment relation - Björn Bartling; Ernst Fehr; Klaus M. Schmidt (University of Zurich, Department of Economics, 2012)
Employment contracts give a principal the authority to decide flexibly which task his agent should execute. However, there is a tradeoff, first pointed out by Simon (1951), between flexibility and employer moral hazard. An employment contract allows the principal to adjust the task quickly to the realization of the state of the world, but he may also abuse this flexibility to exploit the agent. We capture this tradeoff in an experimental design and show that principals exhibit a strong preference for the employment contract. However, selfish principals exploit agents in one-shot interactions, inducing them to resist entering into employment contracts. This resistance to employment contracts vanishes if fairness preferences in combination with reputation opportunities keep principals from abusing their power, leading to the widespread, endogenous formation of efficient long-run employment relations. Our results inform the theory of the firm by showing how behavioral forces shape an important transaction cost of integration - the abuse of authority - and by providing an empirical basis for assessing differences between the Marxian and the Coasian view of the firm, as well as Alchian and Demsetz's (1972) critique of the Coasian approach.
Keywords: C91; D23; D86; M5; 330; theory of the firm; transaction cost economics; authority; power abuse; employment relation; fairness; reputation; Arbeitsbeziehungen; Arbeitsvertrag; Prinzipal-Agent-Theorie; Theorie der Unternehmung; Test